2021
DOI: 10.3389/fphar.2021.688386
|View full text |Cite
|
Sign up to set email alerts
|

Role of Common Genetic Variants for Drug-Resistance to Specific Anti-Seizure Medications

Abstract: Objective: Resistance to anti-seizure medications (ASMs) presents a significant hurdle in the treatment of people with epilepsy. Genetic markers for resistance to individual ASMs could support clinicians to make better-informed choices for their patients. In this study, we aimed to elucidate whether the response to individual ASMs was associated with common genetic variation.Methods: A cohort of 3,649 individuals of European descent with epilepsy was deeply phenotyped and underwent single nucleotide polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It will perform a genome-wide association study (GWAS) on individuals responding to specific ASMs or functionally related groups of ASMs, using non-responders as controls. It will also identify several potential regions of interest, but this will not detect relevant genome-wide loci for the ASM-specific response [ 143 ]. GWAS studies did not show a predictive value of common genetic variants for ASM response status.…”
Section: Currently Used Antiepileptic Drugsmentioning
confidence: 99%
“…It will perform a genome-wide association study (GWAS) on individuals responding to specific ASMs or functionally related groups of ASMs, using non-responders as controls. It will also identify several potential regions of interest, but this will not detect relevant genome-wide loci for the ASM-specific response [ 143 ]. GWAS studies did not show a predictive value of common genetic variants for ASM response status.…”
Section: Currently Used Antiepileptic Drugsmentioning
confidence: 99%
“…Studies are trying to elicit the answers to these questions. For example, the area of pharmacogenomics is growing with the aim of personalising therapies based on an individual’s genetic profile with regard to variants that affect response and AEs [ 307 ]. With this in mind, the HLA-A*11:01 allele has been identified as possibly being associated with LEV-induced psychiatric AEs [ 308 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate rare genetic variants were found in the exome-based research of patients with non-familial non-acquired focal epilepsy and DEPDC5 was regarded as a potential risk factor for drug resistance ( 31 ). For the specific drug response, common genetic variants were not significantly associated with common ASMs in a study containing 3,649 individuals with focal epilepsy or generalized genetic epilepsy ( 32 ). However, an exome-based study targeting rare genetic variants revealed an increased burden of damaging variants in gene groups associated with pharmacokinetics or targeting in patients resistant to valproic acid or levetiracetam ( 33 ).…”
Section: Discussionmentioning
confidence: 99%